Ecological modelling of Spodoptera frugiperda genotypes larval dispersal as tool to understand and management resistance in Bt cotton landscapes - Malaquias, José Bruno (2019)
The demand for information in a systematic way about ecology of target insect species of transgenic plants has increased in recent decades due to the growing interest in this new technology in pest management. Larval mobility in agricultural ecosystems when on occurrence of contamination of Bt crops, intentionally or unintentionally - has been subject of study by several researchers, however information about larval mobility in tropical conditions are still scarce. This scenario created opportunity for hypothesis testing on behavioural aspects of Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae) in landscapes with spatial-temporal co-occurence of Bt and non-Bt cotton plants. The main objective of the current research was to study the larval dispersal of the pest in field and laboratory conditions in order to insert computational modelling components to describe the evolution of resistance to Bt cotton. In the first chapter of this thesis, it is presented a general introduction. In the second one, we studied the feeding behaviour associated with larval dispersal of S. frugiperda genotypes and possible effects on spatial distribution of the resistant individuals in Bt and non-Bt cotton fields. We analyzed in the third chapter the consequences to resistance progress of the dispersal pattern of susceptible, Cry1F-resistant and heterozygous genotypes of S. frugiperda in pure and contaminated artificial landscapes. In the fourth chapter we assessed the impact of the dispersal by ballooning combined with walking dispersal on resistance evolution in conditions of plant mixture with non-Bt and Bt cotton plants in events with high and non-high dose. In the last chapter, we compared the movement dynamics of S. frugiperda genotypes between 28oC and 32oC, and with an individual-based model we analyzed the possibility if one of the genotypes could persist and would lead the other to the exclusion on refuge areas with non-Bt cotton plants. In a general way, faced on the larval dispersal of S. frugiperda genotypes, the results found here highlight the importance of implementation of strategies to avoid contamination through inadequate agronomic practices such as destruction of cotton plants after harvest, volunteer plant control, and seed saving after harvest. All information generated in this thesis could contribute in the optimization of regional resistance management within a concept of insect population control in wide areas.